Anatomia vegetativa de Ctenitis mela nosticta (Dryopteridaceae, Pteridophyta) - Hernandez Hernandez, V.=700 1 Terrazas, T.; Mehltreter, K.
(Es, En)
Ilus., 33 ref
Keywords: DRYOPTERIS; HELECHOS; ANATOMIA DE LA PLANTA; ESCLERENQUIMA; MESOFILO; RAICES; MEXICO; CTENITIS MELANOSTICTA